Online HIV prophylaxis delivery: Protocol for the ePrEP Kenya pilot study - Kiptinness, Catherine; Naik, Paulami; Thuo, Nicholas; Malen, Rachel C.; Dettinger, Julia C.; Pintye, Jillian; Rafferty, Maeve; Jomo, Edwin; Nyamasyo, Nicky; Wood, Tony; Isabelli, Paul; Morris, Sarah; et al. (Frontiers in Public Health, 2023)
Background Online pharmacies in Kenya provide sexual and reproductive health products (e.g., HIV self-testing, contraception) and could be leveraged to increase the reach of HIV pre-exposure and post-exposure prophylaxis (PrEP/PEP) to populations who do not frequently attend health facilities. To date, evidence is limited for operationalizing online PrEP/PEP delivery and the type of populations reached with this differential service delivery model. Methods The ePrEP Kenya Pilot will deliver daily oral PrEP and PEP via MYDAWA, a private online pharmacy retailer, to clients in Nairobi for 18 months. Potential clients will obtain information about PrEP/PEP on MYDAWA's sexual wellness page and self-screen for HIV risk. Individuals ≥18 years, identified as at HIV risk, and willing to pay for a blood-based HIV self-test and PrEP/PEP delivery will be eligible for enrollment. To continue with online PrEP/PEP initiation, eligible clients will purchase a blood-based HIV self-test for 250 KES ( USD 2) [delivered to their setting of choice for 99 KES ( USD 1)], upload an image of their self-test result, and attend a telemedicine visit with a MYDAWA provider. During the telemedicine visit, providers will screen clients for PrEP/PEP eligibility, including clinical concerns (e.g., kidney disease), discuss self-test results, and complete counseling on PrEP/PEP use and safety. Providers will refer clients who self-test HIV positive or report any existing medical conditions to the appropriate services at healthcare facilities that meet their preferences. Eligible clients will be prescribed PrEP (30-day PrEP supply at initiation; 90-day PrEP supply at follow-up visits) or PEP (28-day supply) for free and have it delivered for 99 KES ( USD 1). We will measure PrEP and PEP initiation among eligible clients, PEP-to-PrEP transition, PrEP continuation, and implementation outcomes (e.g., feasibility, acceptability, and costs). Discussion Establishing pathways to increase PrEP and PEP access is crucial to help curb new HIV infections in settings with high HIV prevalence. The findings from this study will provide evidence on the implementation of online pharmacy PrEP and PEP service delivery that can help inform guidelines in Kenya and similar settings.